Programa educativo domiciliario a pacientes con insuficiencia renal crónica aplicando la teoría del autocuidado. Guaranda. período diciembre 2022 – abril 2023. - Pineda Jiménez, Karla De Los Ángeles (2023)
The objective of this project was to design a home educational program for patients with chronic renal failure applying the Theory of Self-Care residents of Guaranda. This descriptive, purposeful and field study used a quantitative approach. The population consisted of 15 patients diagnosed with chronic renal failure in the town. A structured questionnaire-type instrument was used, designed with closed questions related to self-care for patients suffering from chronic renal failure (CRF). The results were processed through tables of frequencies and percentages and indicated the need for information on chronic kidney disease; your patients should pay special attention to personal hygiene and skin care to prevent infection. A home program was designed that includes a guide with recommendations that contribute to improving the quality of life and survival of patients with CKD. Keywords: CKD, Self-care, Complications, Educational Program